ANALYSIS OF THE APPLICATION OF BANA'S RACAK IN THE SUCCESS OF BUDGET IMPLEMENTATION AT CLASS I IMMIGRATION OFFICE PEKANBARU - I.A Prabadhi; Catur Susaningsih; Bagas Agung Laksono (Polteknik Imigrasi, 2022)
In order to realize a successful implementation of the budget, Pekanbaru Immigration Office made an action plan for change in the form of a fund withdrawal application namely Aplikasi Rencana Penarikan Dana (RANCAK BANA). This study uses the Mix-Methods method, namely research conducted by combining quantitative and qualitative approaches. This study focuses on analysing the quality of the RANCAK BANA application through the approach of 6 (six) Delone and McLean Model variables and 7 (seven) HR development indicators. The sampling technique used is purposive sampling by taking an adjusted sample based on the specified criteria. In the data processing and data analysis process, it was carried out using the SmartPLS software to obtain descriptive statistical analysis and use the PLS-SEM procedure. There are 8 hypotheses obtained, including 3 (three) hypotheses and 5 (five) other hypotheses which are rejected / not proven to have an effect, so that the RANCAK BANA application can be said to have good quality. And the role of the immigration office which has been very good at providing a strategy in preparing quality human resources. However, there are still some deficiencies that are expected to be developed and further improved in order to create successful budget execution through this RANCAK BANA Application.